What can the letter Q teach us about Shakespeare? (KULT_online, 2016)
Jeffrey Masten’s new book examines connections between sex, language, and affect in Shakespeare’s time. Masten argues that the traditions of performance, orthography, and textual editing can be used to reveal important facts about gender and sexuality during the Renaissance. Taking a deconstructive approach to a series of key words, the book offers many new perspectives on sexuality and embodiment in British Renaissance culture. It also constitutes an important contribution to queer theory and offers surprising and often insightful readings of many famous plays.